2016
DOI: 10.5350/sleep.hypn.2016.18.0117
|View full text |Cite
|
Sign up to set email alerts
|

Dental Arch Morphology as a Predictor of Sleep Disordered Breathing

Abstract: Objective: There is limited data available regarding dental arch morphology and its association with Sleep Disordered Breathing (SDB). The objective of the study was to compare the dental arch morphology of patients with Obstructive Sleep Apnoea-Hypopnoea Syndrome (OSAHS) and of those without any symptoms of SDB. Patients/Methods: A total of 600 subjects were included in the study and were divided into two groups of 300 subjects each (390 men and 210 women); Group 1: Patient group; Group 2: Control group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The mean upper arch width of the OSA group has also been shown to be narrower in the canine region and wider in the premolar and molar regions when compared to the non-OSA group. 31 Moreover, mandibular arches of the OSA group were narrower in the canine region and wider in the premolar and molar areas. 31 Looking at width and depth independently is not adequate to evaluate arch form because these parameters are affected by arch size as well as by arch form.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The mean upper arch width of the OSA group has also been shown to be narrower in the canine region and wider in the premolar and molar regions when compared to the non-OSA group. 31 Moreover, mandibular arches of the OSA group were narrower in the canine region and wider in the premolar and molar areas. 31 Looking at width and depth independently is not adequate to evaluate arch form because these parameters are affected by arch size as well as by arch form.…”
Section: Discussionmentioning
confidence: 92%
“…31 Moreover, mandibular arches of the OSA group were narrower in the canine region and wider in the premolar and molar areas. 31 Looking at width and depth independently is not adequate to evaluate arch form because these parameters are affected by arch size as well as by arch form. To overcome this limitation, arch form could be represented by a mathematical equation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…High prevalence of malocclusions in relation to the molar/canine region has been reported in the OSA group, with 60% of the OSA subjects demonstrating an Angle's class II malocclusion. 41 Furthermore, a critical evidence-based appraisal by Patel and Nagle 42 substantiated the consistent role of class II malocclusion in the etiopathogenesis of OSA disorder. Considering the multifactorial causes of OSA, it has also been reported that higher incidence of OSA appears to be associated with classes I and II malocclusions.…”
Section: Epidemiologic Panorama Of Malocclusion In Relation To Obstructive Sleep Apneamentioning
confidence: 99%
“…Crossbite and open bite malocclusions and the effects of increased upper airway resistance on the dental arch morphology were shown to be associated with SDB in Brazilian and Finnish children respectively [ 6 , 7 ]. Indian adults with SDB had a dental arch abnormality with 60% of the test subjects having an angle class II malocclusion [ 8 ]. In a previous pilot study by the same authors, the prevalence of SDB in Indian children was reported to be 48.57% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%